Postoperative secondary contralateral arachnoid cyst following rupture and bleeding of intracranial aneurysm: a case report - Hu, Kun; Yu, Yanyan; Yang, Yancong; Li, Huichen; Liao, Jinyuan; Zhong, Huanglian; Jiang, Qiuhua; Liu, Jun; Zeng, Shuiying; Yang, Nan; Zhang, Wenjun (Frontiers in Surgery, 2025)
The simultaneous occurrence of intracranial aneurysms and intracranial arachnoid cysts is a rare clinical observation, with the majority of documented instances demonstrating ipsilateral presentation. In this report, we describe an atypical case involving the development of a secondary arachnoid cyst subsequent to the rupture of an intracranial aneurysm. Notably the cyst was situated contralaterally to the site of the aneurysm rupture and outside the surgical field. The patient's clinical history and imaging studies confirmedcorroborated the secondary nature of the cyst, which is postulated to have resulted from inflammatory responses triggered by a subarachnoid hemorrhage (SAH). The patient underwent neuroendoscopic partial resection of the cyst wall and lateral ventriculostomy, leading to a significant improvement in neurological dysfunction symptoms associated with the secondary arachnoid cyst. Follow-up cranial MRI demonstrated a substantial reduction in the cyst's volume, with no evidence of subsequent hydrocephalus or cyst enlargement. This case enhances the comprehension of the pathophysiological mechanisms underlying the formation of contralateral arachnoid cysts subsequent to aneurysm rupture and emphasizes the necessity of acknowledging arachnoid cysts as potential delayed complications associated with aneurysmal subarachnoid hemorrhage (aSAH).